Bacteria as Potential Indicators of Heavy Metal Contamination in a Tropical Mangrove and the Implications on Environmental and Human Health - Melanie De La Rosa- Acosta; Johannys Jiménez-Collazo; Marixa Maldonado-Román; Karlo Malavé-Llamas; Juan Carlos Musa-Wasil (Journal of Tropical Life Science, 2015)
Heavy metal (HM) exposure has been associated with human health diseases like cancer, kidney and liver damage, neurological disorders, motor skills, low bone density and learning problems. With the beginning of the industrialization the heavy metals in high concentration contributes to put on risk the humans in the vicinity. Our study site is located in Cataño, Puerto Rico, a highly industrialization area that has a recreational park nearby, a rum distillery, two thermoelectric factories, and was impacted by CAPECO (oil refinery) explosion in 2009. Las Cucharillas marsh is part of The San Juan Bay Estuary System, considered as a critical wildlife area because of their location. This mangrove marsh has three of the four mangrove species found in PR Laguncularia racemosa, Avicennia germinans and Rhizophora mangle; species that have the capacity to phytoremediate HM. This study was aimed at seven different heavy metals: Arsenic (As), Cadmium (Cd), Chromium (Cr), Lead (Pb), Zinc (Zn), Mercury (Hg) and Copper (Cu). These metals at high concentrations are of human health concern due to their toxicity, persistence, bioaccumulative and biomagnification potentials. Contamination of surface sediments with HM affects the food chain, starting with marine organisms up to humans. The people who live near the contaminated area and the local fishermen are at high risk of exposure. Studies reveal that certain microorganisms can resist the toxicity of heavy metals even at high concentrations. Our study pretends to exploit the sensitive nature of some bacteria to HM and use them as bioindicators. The objective of this research is to assess the bacterial community on the mangrove marsh, identify these bacteria and correlate bacterial species with the type and concentration of the metals found on the site. Our preliminary results with the BIOLOG® identification were five bacteria that are: Carnobacterium inhibens, Cupriavidus gilardii, Enterococcus maloduratus, Microbacterium flavescens and Ralstonia pickettii. This study will continue with an assessment of the exposure of different concentrations of heavy metals to our identified bacteria and underlying the mechanisms of degradation, magnification and or bioconcentration of these heavy metals.